Determinants of New Firm Formation in Developing Countries: A Review - Daniela Calá, Carla; Arauzo-Carod, Josep-Maria; Manjón-Antolín, Miguel (Senate Hall, 2017)
We address the question of what determines new firm formation in developing countries. Because of the influence that this may have on the design of firm entry policies, our main concern is whether the determinants of new firm formation are the same and/or have the same impact in developed and developing countries. We discuss arguments put forward in the literature that may support the existence of differences in the determinants of firm creation between developed and developing countries. We also analyse the results found on the determinants of formal firm entry in developing countries and compare these results with those found in developed countries. Our main conclusion is that policy makers in developing economies should be careful when using evidence from developed countries to design firm entry-promoting policies. Keywords: firm entry, firm creation, firm dynamics, developing countries JEL: O1; O12; L26; M13
Keywords: firm entry|firm creation|firm dynamics|developing countries